EEG upper/low alpha frequency power ratio relates to temporo-parietal brain atrophy and memory performances in mild cognitive impairment - Moretti, Davide V.; paternicò, donata; Binetti, Giuliano; Zanetti, Orazio; Frisoni, giovanni b. (Frontiers in Aging Neuroscience, 2013)
Objective: temporo-parietal cortex thinning is associated to mild cognitive impairment (MCI) due to Alzheimer disease (AD). The increase of EEG upper/low alpha power ratio has been associated with AD-converter MCI subjects. We investigated the association of alpha3/alpha2 ratio with patterns of cortical thickness in MCI. Methods: 74 adult subjects with MCI underwent clinical and neuropsychological evaluation, electroencephalogram (EEG) recording and high resolution 3D magnetic resonance imaging (MRI). Alpha3/alpha2 power ratio as well as cortical thickness was computed for each subject. Three MCI groups were detected according to increasing tertile values of upper/low alpha power ratio . Difference of cortical thikness among the groups was estimated. Pearson’s r was used to assess the topography of the correlation between cortical thinning and memory impairment. Results: High upper/low alpha power ratio group had total cortical grey matter (CGM) volume reduction of 471 mm2 than low upper/low alpha power ratio group (p